The Effectiveness Time Token Learning Model on Learning Outcomes of Biology Education Students - Rizki Amalia Nur; Pertiwi Indah Lestari; Nurhidayah Nurhidayah; Rika Riyanti (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study aims to determine the effectiveness of the application of the time-token learning model to biology learning outcomes at Universitas Muslim Maros. This type of research is quantitative and uses pre-experimental methods. The form of the pre-experimental method used is a one-group pretest-posttest. To determine the effectiveness of time-token learning, measurement and observation techniques are used. measurement technique by giving essay tests (pre- and post-tests). Based on the t-test calculation results, a sig (2-tailed) of 1.000 0.05 was obtained. Thus, it can be concluded that the application of the time token learning model is effectively used to improve student learning outcomes.